PROFILE OF BLADDER TRANSITIONAL CELL CANCER IN SOETOMO HOSPITAL SURABAYA - Abdih, M. Asro; Djatisoesanto, Wahjoe; Hardjowijoto, Sunaryo (Indonesian Urological Association, 2014)
Objectives: To describe the characteristic of bladder transitional cell cancer (TCC). Material & methods: We reviewed the medical records of patients with bladder TCC admitted in Soetomo General Hospital Surabaya, from January 2008 until December 2012. The data regarding demographic characteristics, clinical presentation and staging, grading and staging based on pathological examinations results, and the management of the cancer.Results: The 126 cases, consisted of 102 men (81%) and 24 women (19%) with its ratio was 4.2 : 1. All male patients were heavy cigarette smokers. Mean age was 57.8 years, peak incidence was50-59 years. Hematuria was the mostfrequent clinical presentation (112 patients, 88.9%), urinary retention and other complaints (12 patients, 9.5%), and chronic dysuria (2 patients, 1.6%). Clinical staging was T1 as NMIBC in 7 patients (5.7%). MIBC consisted of T2 in 37 patients (30.3%), T3 in 35 patients (28.7%), T4 in 43 patients (35.2%). The pathological grading as an high-grade were 74 patients (64.3%). All patients had underwent TURBT for diagnosis and staging, followed by definitive treatment. It consisted of TURBT and chemotherapy bladder instillation in 7 patients (5.6%), radical cystectomy in 13 patients (10.3%), EBRT in 5 patients (4%), MVAC chemotherapy in 24 patients (19%), EBRT and chemotherapy with MVAC in 3 patients (2.4%). There were 74 patients (58.7%) underwent TURBT alone.Conclusion: Bladder TCC was in advanced stage when diagnosed, most of the patients received only TURBT and refused further treatment. Keywords: Bladder transitional cell cancer, characteristics, managements.